FLOW PATTERN STUDY OF FORMED SUCTION INTAKE (FSI) BY MEANS OF COMPUTATIONAL FLUID DYNAMICS (CFD) SIMULATION - Insan Kamil - NIM:25015043, Aozora
Water pumps as one of the most important infrastructures for a wide range of needs depend heavily on the efficiency and quality of the performance of the various components. Vortex with air entrancement, distribution of flow velocity with high deviation at pump throat, and flow angle at pump throat, are some phenomenon which often happened at pump, causing decreasing efficiency and pump performance. Intake is one component of the pump that serves to control the flow patterns that enter into the pump. Formed Suction Intake (FSI) as one type of intake, has become an option in overcoming various adverse effects of incoming flow into the pump. Understanding flow patterns on the FSI becomes quite crucial, while the physical model is very limited in providing a high enough resolution for an observable model as a whole. Simulation with Computational Fluid Dynamic (CFD), provides a higher resolution for better FSI modeling. From the CFD simulation results, it was found that a close correlation between vortex occurrences is characterized by increased vortices in an area with an increase in turbulent parameters such as K production and turbulence intensity. In addition, the incidence of vortex followed by air input into the pump throat appears to be due to draw downs in front of the FSI and followed by a swirl of water around the draw down. Then the propagation from the FSI upstream distribution which is highly affected by the flow separation results in high deviatoin of the velocity distribution at the pump throat.